2007
DOI: 10.1177/10883576070220040601
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Direct Instruction for Teaching Statement Inference, Use of Facts, and Analogies to Students With Developmental Disabilities and Reading Delays

Abstract: This study investigated the effects of a Direct Instruction (DI) reading comprehension program implemented with students who had developmental disabilities, including autism spectrum disorders (ASD) and reading delays. There is little research in the area of reading comprehension for students with ASD and no research as to the effectiveness of reading comprehension DI. A multiple-probe-across-behaviors design was employed. A functional relationship between Direct Instruction and reading comprehension skills an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 15 publications
6
82
0
6
Order By: Relevance
“…This specific population is different from previous studies examining the efficacy of explicit instruction on skills for students with ASD (oral language skills; Gantz and Flores 2009). Additionally, it is possible that students in the current study may have required more intensive and structured support to learn than the students in the Flores and Gantz (2007) and Gantz and Flores (2009) studies. In both contributing studies participants were older (e.g., fifth grade) in comparison to participants in the current study (e.g., Kindergarten-first grade) and authors reported participants' IQs well above those who participated in current study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This specific population is different from previous studies examining the efficacy of explicit instruction on skills for students with ASD (oral language skills; Gantz and Flores 2009). Additionally, it is possible that students in the current study may have required more intensive and structured support to learn than the students in the Flores and Gantz (2007) and Gantz and Flores (2009) studies. In both contributing studies participants were older (e.g., fifth grade) in comparison to participants in the current study (e.g., Kindergarten-first grade) and authors reported participants' IQs well above those who participated in current study.…”
Section: Discussionmentioning
confidence: 81%
“…Explicit instruction is effective for teaching students with high incidence disabilities a variety of skills (Engleman and Carnine 1991;Kame'enui and Simmons 1990;Repp et al 1996;VanLaarhoven et al 2003). In addition, prior studies have shown that students with ASD benefit from explicit instruction in the areas of reading and language (e.g., Flores and Gantz 2007;Gantz and Flores 2009). The current study contributes to the literature in a number of ways.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, DI has positively affected reading decoding (Fredrick et al 2002;Shippen et al 2005) and reading comprehension (Carlson and Francis 2002;Flores and Ganz 2007). DI has improved reading skills in children from elementary (Carlson and Francis 2002;Humphries et al 2005) to middle school (Grossen 2004;Shippen et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…DI has improved reading skills in children from elementary (Carlson and Francis 2002;Humphries et al 2005) to middle school (Grossen 2004;Shippen et al 2005). Additionally, DI has been used successfully with children with a variety of abilities, including autism (Flores and Ganz 2007), epilepsy (Humphries et al 2005), learning disabilities and cognitive impairments (Carlson and Francis 2002), those with limited English proficiency (Carlson and Francis 2002), and students at risk (Carlson and Francis 2002;Grossen 2004).…”
Section: Introductionmentioning
confidence: 98%